Shakespeare broadcast: rethinking the meaning of live performance - Gregório, Paulo da Silva (Sala Preta, 2023)
While live theatre broadcasting has been instrumental in disseminating Shakespearean productions by British institutions such as the National Theatre beyond the physical theatre space, it has raised important questions regarding the primacy of theatre as a privileged medium where Shakespeare is made to re-signify. This article examines theoretical questions regarding the ways in which the markedly intermedial idiom of this genre of Shakespearean adaptation generates new modes of spectatorial participation, reconfiguring notions of liveness and co-participation — conventionally understood as distinctive features of the ontological identity of theatre. These issues will be examined in relation to a British production of Hamlet (2015) directed by Lyndsey Turner for the National Theatre and broadcast live in cinemas as part of the National Theatre Live project. We shall see that, while the filming techniques deployed to capture the live performance seek to reproduce on screen the here-and-now of live theatre, they point to alternative ways of re-signifying the Shakespearean performance on screen both synchronically and asynchronously.